Identification and characterization of a novel abiotic stress responsive OsTHIC gene from rice - Changqiong Hu; Changqian Quan; Jingmin Zhou; Qiang Yu; Zhigang Bai; Zhengjun Xu; Xiaoling Gao; Lihua Li; Jianqing Zhu; Rongjun Chen (Biotechnology & Biotechnological Equipment, 2018)
To better understand the mechanisms of plant abiotic stress responses and identify novel stress-related genes in rice, we performed global expression analysis in indica rice Pei'ai 64S under multiple stresses. Among numerous genes, a gene named OsTHIC was selected, which was highly induced in leaves and panicles in response to all stresses at different developmental stages, especially at the booting stage under cold stress. OsTHIC contains an open reading frame (ORF) of 1920 bp and encodes a predicted protein with 639 amino acid residues. The molecular weight and isoelectric point were predicted to be about 71.31 kD and 6.41, respectively. The results of quantitative real-time polymerase chain reaction (qRT-PCR) analysis were almost identical to those from the GeneChip Rice Genome Array. The sequence alignment showed about 99% similarity to rice phosphate methylpyrimidine synthase. Promoter sequence analysis showed that various stress response-related cis-elements were contained in the promoter region. All the results suggested that OsTHIC may be involved in rice stress responses.